2017
DOI: 10.1177/1048291117740818
|View full text |Cite
|
Sign up to set email alerts
|

Home Health Aides' Perceptions of Quality Care: Goals, Challenges, and Implications for a Rapidly Changing Industry

Abstract: Home care payment models, quality measures, and care plans are based on physical tasks workers perform, ignoring relational care that supports clients' cognitive, emotional, and social well-being. As states seek to rein in costs and improve the efficiency and quality of care, they will need to consider how to measure and support relational care. In four focus groups ( n = 27) of unionized, agency-based New York City home health aides, workers reported aide-client relationships were a cornerstone of high-qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 31 publications
4
70
0
Order By: Relevance
“…Written care plans that clearly specify care tasks are desired by aides and may reflect professionalization that supports aides' safety and job satisfaction. However, the job is much more than the formal tasks captured in a list, care plan, or job description; and the small things that aides do that are not technically part of the job description may make the job more satisfying and safer for aide and client . As aides explained, the “little in‐between things ” that happen in the job outside of what is written explicitly on the care plan are “[l]ittle things that aren't little things, because they are what make the relationship work.”(FG4)…”
Section: Discussionmentioning
confidence: 99%
“…Written care plans that clearly specify care tasks are desired by aides and may reflect professionalization that supports aides' safety and job satisfaction. However, the job is much more than the formal tasks captured in a list, care plan, or job description; and the small things that aides do that are not technically part of the job description may make the job more satisfying and safer for aide and client . As aides explained, the “little in‐between things ” that happen in the job outside of what is written explicitly on the care plan are “[l]ittle things that aren't little things, because they are what make the relationship work.”(FG4)…”
Section: Discussionmentioning
confidence: 99%
“…The researchers used different qualitative research methods in their studies. The majority of studies (N = 9) used focus group interviews as the only method [26][27][28][29][30][31][32][33][34]. Seven studies used face-to-face interviews [35][36][37][38][39][40][41], while five studies used telephone interviews [42][43][44][45][46].…”
Section: Methodological Approachesmentioning
confidence: 99%
“…One study reported that chronic pain and injuries in the lower back, shoulders, knees and neck resulted in surgery [36]. Strenuous work tasks included assisting clients with activities of daily living, performing housekeeping tasks or cleaning [26,32,35,36,42,47], transferring, assisting, repositioning and turning clients [28,32,35,36,42,47,49] and other heavy lifting [28,30,35,36,45,47,49]. Several informants experienced being in danger through physical violence from clients with mental health issues, dementia or Alzheimer's disease [30,32,33,35,36,40,[43][44][45]].…”
Section: Exposure To Physical Demandsmentioning
confidence: 99%
See 2 more Smart Citations